2019
DOI: 10.1128/jvi.02205-18
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Organic Anion-Transporting Polypeptide 1A2, a Novel Avian Hepatitis E Virus (HEV) ORF2-Interacting Protein, Is Involved in Avian HEV Infection

Abstract: Avian hepatitis E virus (HEV) is the main causative agent of big liver and spleen disease in chickens. Due to the absence of a highly effective cell culture system, there are few reports about the interaction between avian HEV and host cells. In this study, organic anion-transporting polypeptide 1A2 (OATP1A2) from chicken liver cells was identified to interact with ap237, a truncated avian HEV capsid protein spanning amino acids 313 to 549, by a glutathione S-transferase (GST) pulldown assay. GST pulldown and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Early report employing HEV-VLPs suggested that attachment of HEV-VLP to cells surface depends on heparin sulfate proteoglycans (HSPGs) and pre-incubation of HEV with heparan sulfate blocks HEV infectivity (Kalia et al, 2009;Yin et al, 2016), whereas sequential research identified asialoglycoprotein receptor (ASGPR) and retinol-binding protein 4 (RBP4) as putative HEV capsids interacting receptors (Shen et al, 2011;Zhang et al, 2016). Meanwhile, a recent study based on avian HEV suggested that organic anion-transporting polypeptide 1A2 (OATP1A2) may be an avian HEV-specific receptor (Li et al, 2019), but whether mammalian counterpart of OATP1A2 acts as potential receptor for mammalian HEV requires further investigation.…”
Section: Open Reading Frame 2 Proteinmentioning
confidence: 99%
“…Early report employing HEV-VLPs suggested that attachment of HEV-VLP to cells surface depends on heparin sulfate proteoglycans (HSPGs) and pre-incubation of HEV with heparan sulfate blocks HEV infectivity (Kalia et al, 2009;Yin et al, 2016), whereas sequential research identified asialoglycoprotein receptor (ASGPR) and retinol-binding protein 4 (RBP4) as putative HEV capsids interacting receptors (Shen et al, 2011;Zhang et al, 2016). Meanwhile, a recent study based on avian HEV suggested that organic anion-transporting polypeptide 1A2 (OATP1A2) may be an avian HEV-specific receptor (Li et al, 2019), but whether mammalian counterpart of OATP1A2 acts as potential receptor for mammalian HEV requires further investigation.…”
Section: Open Reading Frame 2 Proteinmentioning
confidence: 99%
“…Due to the lack of highly effective culture systems in vitro, the life cycle of HEV remains unclear. Using HEV-like particles (HEV-LPs), several host factors have been determined to participate in naked HEV infection, including cell attachment, entry, and/or trafficking (Kamar et al, 2009;Yu et al, 2011;Kapur et al, 2012;Holla et al, 2015;Ahmed et al, 2016;Zhang et al, 2016;Li et al, 2019;Shiota et al, 2019). For example, during clathrinand dynamin-dependent endocytosis, membrane cholesterol, the PI3K pathway, and actin have been shown to participate in cell entry and membrane trafficking of naked HEV particles (Kapur et al, 2012;Holla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The complete HEV genome consists of three open reading frames (ORF): ORF1, ORF2, and ORF3. The ORF2-encoded viral capsid protein generally includes 660 amino acids (aa), although in avian HEV it is only 606 aa in length (Zhao et al, 2015;Fu et al, 2019), it plays a crucial role during viral infection by interacting with host factors (Kamar et al, 2009;Shukla et al, 2011;Kapur et al, 2012;Ahmed et al, 2016;Yin et al, 2016Yin et al, , 2017Li et al, 2019;Sayed et al, 2020). Due to the lack of a highly efficient in vitro cell culture system, two truncated HEV capsid proteins spanning 112-606 aa (Kamar et al, 2009) and 368-606 aa (designated p239) were universally used to screen the host proteins interacting with HEV based on both truncated capsid proteins mimic non-enveloped HEV particles (Yamashita et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a truncated avian HEV capsid protein spanning aa 313-549 (designated ap237) with sequence homology to HEV p239 served as a bait protein to screen for host interaction partners of avian HEV capsid protein (Li et al, 2019). Among screened host factors, organic anion transporting polypeptide 1A2 (OATP1A2) was shown to enhance avian HEV infection of host cells, prompting the creation of a cell line (designated LMH OATP1A2 ) that expressed OTAP1A2 (Li et al, 2019). Meanwhile, another host factor, a small Rho family GTPase, known as cell control protein 42 (CDC42), was also pulled down by ap237 (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation